2007
DOI: 10.1007/s11270-007-9543-5
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic Aromatic Hydrocarbons (PAH) in Water and Sediment from Gully Pots

Abstract: A gully pot is often cleaned with the help of an eductor truck, which uses hydrodynamic pressure and a vacuum to loosen and remove the solids and standing liquid from a gully pot. This paper considers the polycyclic aromatic hydrocarbons (PAH) content in the gully pot mixture (water and sediment) after it has been discharged from the eductor truck. The results show that most PAH was attached to particles, and the dissolved phase represented approximately 22% of the total water concentration. No significant dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 31 publications
1
42
1
Order By: Relevance
“…The most abundant individual PAHs were naphthalene, phenanthrene, fluoranthene and pyrene. Jartun et al (2008) measured the combined 16 PAH concentrations in sediments collected from stormwater traps and detected a mean value of 7.6 µg g -1 which was comparable with that reported by Karlsson and Viklander (2008b). This study also analysed a combined total of 7 PCB congeners in gully pot sediments and found much lower levels represented by a mean concentration of 0.08 µg g -1 and a range of <0.0004 µg g -1 to 0.704 µg g -1 .…”
Section: Gully Potssupporting
confidence: 83%
See 1 more Smart Citation
“…The most abundant individual PAHs were naphthalene, phenanthrene, fluoranthene and pyrene. Jartun et al (2008) measured the combined 16 PAH concentrations in sediments collected from stormwater traps and detected a mean value of 7.6 µg g -1 which was comparable with that reported by Karlsson and Viklander (2008b). This study also analysed a combined total of 7 PCB congeners in gully pot sediments and found much lower levels represented by a mean concentration of 0.08 µg g -1 and a range of <0.0004 µg g -1 to 0.704 µg g -1 .…”
Section: Gully Potssupporting
confidence: 83%
“…There have been few reports of the behaviour of specific organic pollutants within the gully pot system although Karlsson and Viklander (2008b) found the PAHs within a gully pot mixture to be predominantly particulate associated achieving combined concentrations for 16 PAHs of 10 µg g -1 in the sediment phase. The most abundant individual PAHs were naphthalene, phenanthrene, fluoranthene and pyrene.…”
Section: Gully Potsmentioning
confidence: 99%
“…During the rainy season, it is expected that dissolution and washing-off of the PAHs from the soil matrix could occur (Karlsson & Viklander, 2008;Morillo et al, 2008). The highest concentrations of PAHs were recorded for BaA in Pt5 (0.021) and Pt6 (0.015), these points had about twice and more the concentrations of PAHs than in the other points.…”
Section: Resultsmentioning
confidence: 99%
“…Significant differences and correlations were acenaphthylene, phenanthrene, fluorene and anthracene in fish may also be attributed to their higher solubility in water compared to HMW PAHs [36]. Therefore, LMW PAHs are readily bioavailable through fish gill and skin diffusion whereas the HMW PAHs attach to particles and sediment and must be consumed through diet [32,35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Naphthalene is predominantly derived from anthropogenic sources such as oil and gas drilling, crude oil, petroleum refining and bitumen among others [16,21]. Therefore, the high abundance of naphthalene relative to other PAHs may be due to its high input into the environment through industrial and domestic emissions [34], in particular petroleum sources [35]. In addition, the higher concentrations of LMW PAHs such naphthalene, Identification of target analytes were based on the matching of sample peak area and the retention time (RT) to that of reference standard, allowing a RT tolerance intervals of 2.5% to 4% (of the reference standard) within same analytical batch.…”
Section: Pahs In S Lalandimentioning
confidence: 99%